The Role of PI3K in Met Driven Cancer: A Recap - Hervieu, Alexia; Kermorgant, Stéphanie (Frontiers in Molecular Biosciences, 2018)
The Receptor Tyrosine Kinase (RTK) Met, overexpressed or mutated in cancer, plays a major role in cancer progression and represents an attractive target for cancer therapy. However, in cancer therapy, RTK inhibitors can lead to drug resistance explaining the necessity to develop therapies targeting downstream signalling or to target multiple signalling pathways simultaneously. Phosphatidylinositide 3-Kinase (PI3K) is one of the most deregulated pathways in cancer and is implicated in various types of cancer. PI3K signalling is also a major signalling pathway downstream of RTK, including Met. Its major effectors include Akt and “mechanistic Target of Rapamycin” (mTOR), which each play key roles in numerous and various cell functions. Thanks to the development of molecular and pharmaceuticals tools, we are now able to dissect the roles of each of them independently. In this review, we summarise the current understanding of the activation and role of PI3K/Akt/mTOR downstream of Met in cancer.